Does Indonesia's High Level of Corruption Affect Its Trade Volume? - Yunan, Zuhairan Yunmi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
This article aims to examine the connection between corruption and the amount of trade in several commodities, including raw materials, capital goods, intermediate products, and consumer goods, with a specific emphasis on the Indonesian situation. Indicators of corruption utilized in this article include the Corruption Perception Index (CPI) and the Control of Corruption (COC). Meanwhile, the sum of Indonesia's exports and imports indicated the country's trade volume. For this issue, this article employs the gravity model and regresses it with either a fixed effect or a random effect model. The empirical findings show that both the CPI and COC levels of corruption in Indonesia have a negative impact on the amount of trade in capital goods. However, only the CPI shows a negative correlation with the prevalence of corruption in Indonesia, whereas consumer products, intermediate goods, and raw materials all show a positive correlation. The impact of COC on Indonesia's trade partners is complicated for the commodities this article looked at. The insights generated from this study hold significant value in shaping a more informed and accurate representation of how corruption permeates and impacts international trade dynamics, thus contributing to a more nuanced understanding of this critical issue.JEL Classification: D73, F10, C01How to Cite:Yunan, Z. Y. (2023). Does Indonesia’s High Level of Corruption Affects Its Trade Volume? Signifikan: Jurnal Ilmu Ekonomi, 12(2), 425-440. https://doi.org/10.15408/sjie.v12i2.35156.